KEPADATAN ASCIDIACEA (DIDEMNUM MOLLE) DI PERAIRAN PANTAI TASIK RIA, SULAWESI UTARA - Dewanto, Didit Kustantio (Sekolah Tinggi Perikanan dan Kelautan (STPL) Palu, 2016)
This research was conducted with the aim of knowing the density of Ascidiacea D. molle located in Tasik Ria, Manado Bay, North Sulawesi. Collecting data and samples using diving equipment (SCUBA) with quadrant and transect method, placed in the 50 meters parallel to the shoreline. The first transect placed at a depth of 5 meters and second transect at a depth of 3 meters. In calculating the density of D. molle using a quadrant with a size of 50 x 50 cm placed on a transect at ten points. Average density D. molle at a depth of 5 meters higher than at a depth of 3 meters and vary in each month. This trend is strongly influenced by various environmental factors are not yet known, so it takes a period of time longer observation with an emphasis on the relationship between environmental factors and the frequency of  attendance D. molle.